PENGGUNAAN PAPEC DI MATA PELAJARAN MATEMATIKA: APAKAH ITU BERPENGARUH PADA HASIL BELAJAR SISWA KELAS IV? - Apriyanti, Melina; Hasanah, Viena Rusmiati; Sausan, Inas (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
he purpose of this study was to determine the increase in student learning outcomesby using PAPEC class IV SD learning media for mathematics subjects related to fractionsdirectly. This study used a quantitative approach method that was useful for testing of media onfraction material, specifically equivalent fractions and simplification of fractions that supportstudent learning outcomes. The subjects of this study were fourth-grade students of SDN Sukasari03 Kec. Pameungpeuk, using a research instrument in the form of a descriptive test. Based on thedata obtained, the researcher found that 82.7% of fourth-grade students could effectively andsuccessfully solve fraction problems, which exceeded the minimum standard of 80%. During cycle1, only 58.6% of students met the minimum standard, so the study was repeated during cycle 2and achieved a percentage of 82.7%. Based on the results of the study, it can be concluded thatPAPEC learning media can improve student learning outcomes and can be used as a referencefor mathematics teachers in fractional learning.